Ensino de pontuação em coleções didáticas de português: uma análise dialógica - Silva, Anderson Cristiano da (2015)
At the end of primary school too many students leave primary school with gaps in reading and writing skills. Concerning the writing skill and despite the difficulties found, there is the ability of using punctuation mark as well as the lack of knowledge about this linguistic resource for the constitution of senses in the text. This specific learning difficulty is the result of multiple elements which we can emphasize one: the teaching proposals for punctuation in mother tongue pedagogical materials in circulation. Thus, our motivation arose mainly concerning the punctuation marks which are covered in Portuguese textbooks of elementary school, approved by the Programa Nacional do Livro Didático (PNLD) and distributed in Brazilian public schools. Thus, this study lays on a reflection on the subject, revealing a way to question the educational-methodological approaches, therefore allowing new perspectives, whose results may contribute to the expansion of this topic in the field of Applied Linguistics and Language Studies. This research aims at analyzing the punctuation marks activities in of two textbook collections (6th - 9th grade): Português: uma proposta para o letramento, by Magda Soares, and Português: linguagens, by William Roberto Cereja and Thereza Cochar Magalhães. In this case, we have established some important research questions: (1) What theoretical and methodological guidelines are offered by the two collections for the teaching of punctuation marks in the final years of elementary school? (2) How do they link (or not) to the readers´ formation and producers of texts in the textbooks analyzed, according to official documents guidelines? These questions are related to the guiding assumption that the punctuation activities, present in two collections selected for this research, cannot contribute to the complete development of the writing competence, specifically for the proper use of punctuation marks. Based on this proposition, our thesis is that the two selected collections show unsatisfactory educational approaches related to punctuation, not fitting with the requirements of the official documents, developing critical thinking partially and the ability of proper use of punctuation marks on writing. To support our research, specifically related to the existing types of dialogical relations between didactic approaches on punctuation and expository plot involved in its constitution, the research has as theoretical framework the contributions of Dialogic Discourse Analysis, electing some key concepts developed by Bakhtin and the Circle, such as: utterance and dialogical relations. From the organizational perspective, it was proposed two axes. In the theoretical axis, we present the state of knowledge on punctuation topic by seeking them on last decades of Brazilian academic production. In a second step, we construct the description of the research context, collection and delimitation of the corpus. In practical axis, we started the description and analysis of dialogic educational activities about punctuation teaching in both listed collections, as well as the utterances that parameterize the constitution of these works. Our considerations show considerable differences in approach to punctuation between the two collections, which include: the heterogeneous distribution of content in different school years, lack of coordination between the content and textual production proposals as well as the emphasis given to the oral modality in the exercises at the collection Português: uma proposta para o letramento